A Step to VAR: The Vision Science of Offside Calls by Video Assistant Referees. (December 2020) - Mather, George
The Video Assistant Referee (VAR) system has had a major impact on decision-making in professional association football. However, offside decisions remain a major area of dispute and debate, with over 34 goals ruled out in the first season of VAR in the Premier League. Evidence in vision science points toward two problems with the application of the offside law in VAR, due to their use of a live TV video feed in reviews. First, due to physical and perceptual limits on spatial resolution, there is a significant probability that the spatial positions of the ball and players as judged by VAR will be several centimetres to one side of their true positions. Second, the 50 Hz TV update rate means that judgements of the time-of-contact between player and ball will on average be 10 ms too late, which translates into an increased likelihood of offside calls in fast-moving play. Suggestions are made for how to compensate for these problems during decision-making.